Impact of FDI absorptive capacity on labor productivity in Vietnam - Hung, Tran Khanh; Binh, Dang Thai; Trang, Tieu Van; Hoa, Hoang Van; Anh, Do Quynh; Tu, Pham Huy (Journal of Social Economics Research, 2024)
This study examines the impact of Foreign Direct Investment (FDI) absorptive capacity on labor productivity in Vietnam’s vibrant and dynamic context. Using panel data analysis of firm-level data from the Vietnam Enterprise Survey for 2008-2018, which was collected by the General Statistics Office of Vietnam, the authors find out that capacity is essential in enhancing labor productivity in Vietnamese firms. The study takes a strong and thorough approach, using panel data analysis to find out the many aspects of firm-level absorptive capacity and what these aspects mean for improving labor productivity in Vietnamese businesses. Specifically, firms with higher absorptive capacity tend to have higher labor productivity levels than those with lower absorptive capacity. Our findings suggest that policy makers in Vietnam and other developing countries must develop their absorptive capacity to benefit from FDI and fully improve productivity. In order to fully benefit from foreign direct investment (FDI), host nations must place a high priority on building their capacity to absorb FDI through wise expenditures in infrastructure, innovation, education, and training, as well as intellectual property rights protection. The study also shows how important absorptive capacity is in the relationship between FDI and productivity by adding to the existing research and finding the specific absorptive capacity indicators that are most useful for increasing labor productivity in Vietnamese businesses.